Differentiating mindfulness-integrated cognitive behavior therapy and mindfulness-based cognitive therapy clinically: the why, how, and what of evidence-based practice - Francis, Sarah E. B.; Shawyer, Frances; Cayoun, Bruno A.; Grabovac, Andrea; Meadows, Graham (Frontiers in Psychology, 2024)
It is important to be able to differentiate mindfulness-based programs in terms of their model, therapeutic elements, and supporting evidence. This article compares mindfulness-based cognitive therapy (MBCT), developed for relapse prevention in depression, and mindfulness-integrated cognitive behavior therapy (MiCBT), developed for transdiagnostic applications, on: (1) origins, context and theoretical rationale (why), (2) program structure, practice and, professional training (how), and (3) evidence (what). While both approaches incorporate behavior change methods, MBCT encourages behavioral activation, whereas MiCBT includes various exposure procedures to reduce avoidance, including a protocol to practice equanimity during problematic interpersonal interactions, and a compassion training to prevent relapse. MBCT has a substantial research base, including multiple systematic reviews and meta-analyses. It is an endorsed preventative treatment for depressive relapse in several clinical guidelines, but its single disorder approach might be regarded as a limitation in many health service settings. MiCBT has a promising evidence base and potential to make a valuable contribution to psychological treatment through its transdiagnostic applicability but has not yet been considered in clinical guidelines. While greater attention to later stage dissemination and implementation research is recommended for MBCT, more high quality RCTs and systematic reviews are needed to develop the evidence base for MiCBT.